The vocabulary on the contrition in the fifteenth century Castile - Teodoro, Leandro Alves [UNESP] (Coimbra University Press, 2019)
In the fifteenth century, in order to purify the souls and reform the conduct of the lay faithful, the ecclesiastical leadership of the Crown of Castile began to promote, in a more intense and orderly way, the production of pastoral works in the vernacular language. With emphasis on this production, especially on the sermons given by Saint Vicente Ferrer in Castile, the aim of this work is to analyze the extent to which these moralizing guides helped to naturalize a specific vocabulary of exercises designed for the correction of sins. In other words, this study seeks to question the way these works sought to teach the faithful the salutary role of contrition in the proceedings of redemption of faults, that is to say, the very act of externalizing repentance. Starting from the words used to name the forms of contrition prescribed at that time, another aim of the work is to question how believers could understand these words and broaden their vocabulary about terms concerning the spiritual universe.
O vocabulário da contrição na Castela do século XV
Keywords: Castile; Contrition; Middle Ages